MYTHOLOGICAL ELEMENTS IN GOD OF WAR VIDEO GAME: A POPULAR CULTURE ANALYSIS - Herryawan, Arya Pratama; Winardi, Yohanes Kurniawan; Trihastutie, Nopita (Seminar Nasional Ilmu Terapan, 2024)
Nowadays popular culture can come in many different kinds of forms and platforms and can be accessed by many people, since it is mass-produced, and can be accepted by the people from all classes. According to Abhishek Kumar Singh (2022) popular culture means a culture that can be accepted by the society of all ages.This study aims to analyze the accuracy of heroism in a character named Kratos, who serves as the protagonist and the only controllable character in the God of War video game, using qualitative research methods, this study explores how, no matter how brutal is he, this weird bald man still have the heroic side inside him, along with the accuracy of the mythological elements inside. It is important to remember the significance of analyzing character traits in video games.